2010
DOI: 10.4236/fns.2010.11001
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Bicarbonate—A Potent Ergogenic Aid?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…As mentioned earlier, studies assessing HCO 3 − supplementation have most commonly used HCO 3 − at a concentration is 0.3 g/kg BM [38, 4043]. It has been found that longer-term supplementation at this and lower dosage levels result in improved gastrointestinal tolerance [4446]. The dosage applied in this study was 0.2 g/kg BM, which, according to the study by Bishop et al (2005), could effectively elevate the blood HCO 3 − level without causing negative gastrointestinal reactions [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, studies assessing HCO 3 − supplementation have most commonly used HCO 3 − at a concentration is 0.3 g/kg BM [38, 4043]. It has been found that longer-term supplementation at this and lower dosage levels result in improved gastrointestinal tolerance [4446]. The dosage applied in this study was 0.2 g/kg BM, which, according to the study by Bishop et al (2005), could effectively elevate the blood HCO 3 − level without causing negative gastrointestinal reactions [56].…”
Section: Discussionmentioning
confidence: 99%
“…Dose-response studies assessing commonly used HCO 3 − doses, typically ranging from 0.1–0.5 g/kg body mass (BM), found that the most commonly used dose was 0.3 g/kg BM [38, 4043]. Studies have also shown that chronic supplementation at doses lower than 0.3 g/kg BM results in better gastrointestinal tolerance than one-time acute and larger HCO 3 − supplementation dose before exercise [4446].…”
Section: Introductionmentioning
confidence: 99%
“…However, experts predict it will take minimum one year to be available in the market [6]. The metabolic acidosis can be managed using sodium bicarbonate intravenously between 7.5 -8.4%, while as over-dosage can lead other metabolic abnormalities [23,[59][60][61][62].…”
Section: Probable Effects Of Sodium Bicarbonate To Circumvent Covid-1mentioning
confidence: 99%
“…É um constituinte normal do organismo, sendo responsável pelo equilíbrio ácido-base. Apresenta-se como um sólido cristalino, na forma de pó branco, inodoro, com sabor ligeiramente salgado e alcalino, podendo ser produzido sinteticamente [6,9,10,11]. Pode também ser obtido através do processo de Solvay.…”
Section: Introductionunclassified